Assistant Doctor Adnan Abdullah Hammadi Ministry of Education - Open Educational College (Journal of the College of Basic Education, 2022)
South African society is characterized by the fact that it consists of different groups in origin, culture, religion and color, as these groups descend to African, European or Asian origins, as well as the people of color who came as a result of the mixing of these ethnic groups. An ethnicity trying to relate to the society from which it descended. The South African society is a suitable environment for the growth of the idea of ​​racism and its practice in the social, economic and political reality. The population of South Africa consists of four ethnic components: Africans (79%), whites (10%), colored people (8%), and Asians (3%). And that these groups find their extension within other neighboring countries, and these extensions play important roles in relation to their relations with neighboring countries, negatively and positively.